Spatially-aggregated temperature derivatives: Agricultural risk management in China - Lu Zong; Manuela Ender (International Journal of Financial Studies, 2016)
In this paper, a new form of weather derivative contract, namely the climatic zone-based growth degree-day (GDD) contract, is introduced. The objective is to increase the risk management efficiency in the agricultural sector of China and to reduce the model dimension of multi-regional temperature-based weather derivatives pricing. Since the proposed contract serves as a risk management tool for all of the cities in the same climatic zone, we compare the risk hedging power between the climatic zone-based and the city-based GDD contracts. As a result, we find that the differences between the two types of temperature-based weather contracts are maintained within a certain range.
Keywords: C32; C61; G12; Q14; 330; agriculture; growth degree-day; risk management; weather derivatives